2020
DOI: 10.9744/ijbs.3.1.18-22
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Inflation Rate, Exchange Rate, Corruption Control, and Political Stability to Indonesian Government Bond Yield

Abstract: As a developing country that still has to develop in all fields and to maintain its economic development, the Indonesian government requires significant funds for development. To fulfill the lack of funds obtained from the tax, the Indonesian government sells bonds. Indonesia's 10-year government bonds are known as Surat Utang Negara (or abbreviated as SUN). This study aims to confirm whether the inflation rate, exchange rate, political stability, and corruption control affect the yield of SUN. The research us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This is in line with a study in the Middle East that states that political stability is essential for Yemen's future economic growth (Musibah et al, 2015). The study results in sub-Saharan Africa even added another factor besides macroeconomics and political stability needed to attract foreign investment, which is institutional credibility (Cleeve, 2012;Tjandrasa et al, 2020). Research conducted in Indonesia also concluded that foreign investors are very sensitive to political conditions (Tjandrasa, 2019).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is in line with a study in the Middle East that states that political stability is essential for Yemen's future economic growth (Musibah et al, 2015). The study results in sub-Saharan Africa even added another factor besides macroeconomics and political stability needed to attract foreign investment, which is institutional credibility (Cleeve, 2012;Tjandrasa et al, 2020). Research conducted in Indonesia also concluded that foreign investors are very sensitive to political conditions (Tjandrasa, 2019).…”
Section: Introductionsupporting
confidence: 85%
“…One of the factors that are often considered from a particular country or region is the political development in the country because multinational companies face a great risk stemming from the uncertainty of the political situation in the destination country. Commonwealth Bank's Head of Wealth Management &Client Growth, Ivan Jaya, said Indonesia was a global investor's leading investment destination but hoped for stable Indonesian political conditions (Wuryasti, 2019;Tjandrasa et al, 2020). Associate Director of Colliers Inter-national Indonesia, Ferry Salanto, said many investors were delaying their investments ahead of the general election.…”
Section: Introductionmentioning
confidence: 99%